PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR GEOGRAFI FKIP UNIVERSITAS LAMPUNG - Windarsih Windarsih; I Gede Sugiyanta; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2014)
The aim of this research is: (1) to know the intencity of using internet as one of geography learning source in Geographic Study Program, Teachers Training and Education Faculty, at University of Lampung Years 2011. (2) to see student motivation in using internet as geography learning source in Geographic Study Program, Teachers Training and Education Faculty, at University of Lampung Years 2011. The method used descriptive methodology. The population was 40 student. Based on the research, it can be seen that: (1) intencity of using internet as learning resourches is about 10-40 hours every month. It belongs to medium rate (medium users). (2) student motivation in using internet as learning resourches belongs to medium rate.Penelitian ini bertujuan untuk: (1) mengetahui intensitas pemanfaatan internet sebagai sumber belajar mahasiswa Program Studi Pendidikan Geografi Jurusan Pendidikan IPS FKIP Universitas Lampung Angkatan 2011. (2) untuk mengetahui motivasi mahasiswa Program Studi Pendidikan Geografi Jurusan Pendidikan IPS FKIP Universitas Lampung angkatan 2011 dalam memanfaatkan internet sebagai sumber belajar.Populasinya berjumlah 40 mahasiswa. Berdasarkan hasil penelitian diketahui bahwa: (1) intensitas pemanfaatan internet sebagai sumber belajar mahasiswa sebanyak 10-40 jam per bulan, pemanfaatan ini tergolong sedang (medium user.) (2) motivasi mahasiswa memanfaatkan internet sebagai sumber belajar tergolong motivasi sedang.Kata kunci: geografi, pemanfaatan internet, sumber belajar.